Genetic Diversity Impacts Climate‐Induced Species Range Shifts - Brunno F. Oliveira; Romain Bertrand; Lise Comte; Jonathan Lenoir; Gaël Grenouillet; Lesley T. Lancaster; Jérôme Murienne; Sarah Diamond; Brett R. Scheffers; R. M. W. J. Bandara; Jake A. Lawlor; Nikki A. Moore; et al. (Ecology Letters, 2026)
Climate change threatens biodiversity when species cannot tolerate, adapt to, or track shifting environmental conditions to stay within their climatic niches. A major unresolved question is whether and how species' genetic diversity modulates these dynamics, buffering against range contractions or facilitating range expansions. To test this, we integrated the largest global databases of species range shifts and genetic diversity, encompassing 4673 range shift estimates for 1888 species with available genetic data, including insects, arachnids, birds, fish, and plants. We found that range shifting rates were significantly shaped by the interaction of genetic diversity and climate change velocity. Under rapid warming, species with higher genetic diversity exhibited reduced trailing edge contractions, likely reflecting enhanced evolutionary potential or reduced vulnerability to drift. Under moderate warming, species with higher genetic diversity shifted more rapidly at leading edges and range centroids, consistent with greater colonisation ability. Our study provides evidence that genetic diversity potentially enables persistence at the trailing edge and colonisation at the leading edge, with the magnitude of these effects varying depending on the velocity of climate change.